Peningkatan Caring Islami Pada Perawat - Yousriatin, Fajar; Kirana, Wahyu; Anggreini, Yunita Dwi; Juliana, Diena; Safitri, Dewin; Afrianti, Femi Yuli (FKM UIN Sumatera Utara Medan, 2023)
Nurses are the largest human resource in health services in hospitals, where nurses work 24 hours a day in rotation and continuously to provide comprehensive and professional nursing care and are ready to help patients at any time. In an effort to improve the quality of health services, nurses are required to provide the best service in the form of caring behavior or caring attitude towards others. Caring behavior given by nurses to clients can increase patient satisfaction, especially by incorporating Islamic values where Islamic values are rahmatan lil alamin or compassion for all beings regardless of race, ethnicity, nation, language and religion. RSU Yarsi Pontianak is an Islamic-based hospital in providing nursing care. In accordance with the hospital's vision